2016
DOI: 10.1136/bjophthalmol-2015-308237
|View full text |Cite
|
Sign up to set email alerts
|

Functional impairment of reading in patients with dry eye

Abstract: Dry eye is associated with slower out-loud and silent reading speeds, providing direct evidence regarding the functional impact of dry eye. Reading speed represents a measurable clinical finding that correlates directly with dry eye severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 34 publications
2
28
1
2
Order By: Relevance
“…It is estimated to affect approximately 5% to over 50% of the population, depending on the diagnostic criteria, sex, and age. 1 , 2 DED is a symptomatic disease that combines ocular surface pain or discomfort and impaired visual function, 3 , 4 which greatly decreases patient quality of life. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…It is estimated to affect approximately 5% to over 50% of the population, depending on the diagnostic criteria, sex, and age. 1 , 2 DED is a symptomatic disease that combines ocular surface pain or discomfort and impaired visual function, 3 , 4 which greatly decreases patient quality of life. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…The impact of DED on vision also has functional implications to daily activities and quality of life. Studies have shown that reading rates are significantly reduced in DE patients vs control subjects, and deteriorating visual function correlated with DED severity [ 19 , 20 ]. This suggests that reduced visual function associated with DED can interfere with daily visual activities and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…32,155,160 In particular, the vision-related quality of life is significantly influenced by dry eye owing to impairment of reading ability. [17][18][19] Although scarce, the existing data on the economics of dry eye suggest that the economic impact is substantial. Direct medical costs (e.g., office visits, prescription and over-thecounter medications, specialized eyewear, humidifiers, in-office procedures), direct nonmedical costs (e.g., patient transportation), indirect costs (e.g., lost work time and productivity, changes in type of work), and intangible costs (e.g., reduced quality of life, lost leisure time, impaired social, emotional, and physical functioning) determine the total cost of dry eye to the patient as well as to society.…”
Section: Socioeconomic Considerationsmentioning
confidence: 99%
“…15 Even though these symptoms often improve with treatment, the disease usually is not curable, which may be a source of patient and physician frustration. Importantly, dry eye is also a cause of reduced visual function [16][17][18][19] and may compromise results of corneal, cataract, and refractive surgery.…”
Section: Introductionmentioning
confidence: 99%